Gene expression modulation and the molecular mechanisms involved in Nelfinavir resistance in Leishmania donovani axenic amastigotes. Issue 3 (5th July 2013) - Kumar, Pranav; Lodge, Robert; Raymond, Frédéric; Ritt, Jean‐François; Jalaguier, Pascal; Corbeil, Jacques; Ouellette, Marc; Tremblay, Michel J.
Summary: Drug resistance is a major public health challenge in leishmaniasis chemotherapy, particularly in the case of emerging Leishmania /HIV‐1 co‐infections. We have delineated the mechanism of cell death induced by the HIV‐1 protease inhibitor, Nelfinavir, in the Leishmania parasite. In order to further study Nelfinavir– Leishmania interactions, we selected Nelfinavir‐resistant axenic amastigotes in vitro and characterized them. RNA expression profiling analyses and comparative genomic hybridizations of closely related Leishmania species were used as a screening tool to compare Nelfinavir‐resistant and ‐sensitive parasites in order to identify candidate genes involved in drug resistance. Microarray analyses of Nelfinavir‐resistant and ‐sensitive Leishmania amastigotes suggest that parasites regulate mRNA levels either by modulating gene copy numbers through chromosome aneuploidy, or gene deletion/duplication by homologous recombination. Interestingly, supernumerary chromosomes 6 and 11 in the resistant parasites lead to upregulation of the ABC class of transporters. Transporter assays using radiolabelled Nelfinavir suggest a greater drug accumulation in the resistant parasites and in a time‐dependent manner. Furthermore, high‐resolution electron microscopy and measurements of intracellular polyphosphate levels showed an increased number of cytoplasmic vesicular compartments known as acidocalcisomes in Nelfinavir‐resistant parasites. Together these results suggest that Nelfinavir is rapidly and dramatically sequestered in drug‐induced intracellular vesicles.